A basic study for estimation of occlusal force using an ear wearable sensor. Issue 11 (28th August 2018) - Taniguchi, Kazuhiro; Kurosawa, Mami; Kimura, Yutaka; Nishikawa, Atsushi
Abstract: We aim to develop earphone type wearable devices for measuring occlusal force. In this article, we investigated the correlation between occlusal force and the movement of the ear canal as a basic study to estimate the occlusion force. The proposed estimation method uses the least squares method and the weighted average. We developed an experimental device for simultaneously measuring occlusal force and the movement of the ear canal. This device primarily consists of an occlusal force sensor and a wearable ear sensor, and converts analog signals from both sensors into digital signals using an analog‐to‐digital (AD) converter, then records the data as signals associated with measurement time. The experiment involved six subjects, who performed chewing of the occlusal force sensor five times, for 2 seconds. The occlusal force sensor was placed at the right second molar, with the wearable ear sensor placed on the right ear. Through the experiment, the occlusion and the ear canal movement were found to have a strong correlation. The average correlation coefficients consistently exceeded 0.89 for all subjects.